2010
DOI: 10.1177/154193121005401216
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Observational Tool for Reliably Identifying Work System Factors in the Operating Room that Impact Cardiac Surgical Care

Abstract: The objective of this study is to develop a reliable Tablet-PC based observational tool for identifying work systems factors that impact cardiac surgical care. Using the tool we observed 26 open heart surgeries over a five-month period. In thirteen of the 26 observations, both observers stood in the same location and in the other thirteen cases the observers stood in different locations within the operation room (OR). The surgical cases typically last five hours and were conducted in multiple operating rooms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Using a Tablet-PC data collection tool based on a previous version described elsewhere (Blocker et al, 2010); information about any event that disrupted the flow of the trauma care process was collected. Flow disruptions were time-stamped and categorized by observers in real time according to (1) type of flow disruption; (2) the potential and/or actual impact of the flow disruption on a scale from 1 to 5(1=no impact; 2=acknowledge/no delay; 3= momentary delay; 4=moderate delay; 5=full case cessation); (3) the trauma team member affected by the flow disruption; (4) the description of the flow disruption; and (5) the location of the observer.…”
Section: Methodsmentioning
confidence: 99%
“…Using a Tablet-PC data collection tool based on a previous version described elsewhere (Blocker et al, 2010); information about any event that disrupted the flow of the trauma care process was collected. Flow disruptions were time-stamped and categorized by observers in real time according to (1) type of flow disruption; (2) the potential and/or actual impact of the flow disruption on a scale from 1 to 5(1=no impact; 2=acknowledge/no delay; 3= momentary delay; 4=moderate delay; 5=full case cessation); (3) the trauma team member affected by the flow disruption; (4) the description of the flow disruption; and (5) the location of the observer.…”
Section: Methodsmentioning
confidence: 99%
“…These types are referred to as types 1 to 10 (corresponding to states 1 to 10) in this study, as shown in Table I. Using a Tablet-PC data collection tool [6], information about flow disruptions in the trauma care process is collected. A total of 1759 flow disruptions are identified across 87 trauma cases during a tenweek period.…”
Section: A Model Developmentmentioning
confidence: 99%
“…Several tools and methodologies have been developed and applied in surgery to quantify interruptions in surgical procedures (Zheng et al 2008;Parker et al 2010;Sutton et al 2010;Blocker et al 2010). Parker et al (2010) developed a surgical flow disruption tool that categorizes disruption events into 1) technical factors, 2) environmental factors, 3) technology and instruments, 4) training and procedures, 5) teamwork, and 6) others.…”
Section: Introductionmentioning
confidence: 99%
“…Parker et al (2010) developed a surgical flow disruption tool that categorizes disruption events into 1) technical factors, 2) environmental factors, 3) technology and instruments, 4) training and procedures, 5) teamwork, and 6) others. Using similar disruption categories, Blocker et al (2010) created a tablet-based application that observers used to quantify disruptions in cardiac surgery. Video techniques have also been developed and successfully applied to identify laparoscopic surgery disruptions.…”
Section: Introductionmentioning
confidence: 99%